ANALYSIS OF THE CURRENT STATE OF DEVELOPMENT OF GNSS-OBSERVATION NETWORKS - Korenets, Oleksandr; Lukiianchuk, Anatolii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The purpose of the study is to carry out a scientific analysis of the current state of development of GNSS observation networks. Through the well-founded use of various methods of analysis, the work highlights key aspects of the functioning of these networks, current development trends and identifies possible prospects for their further use, including for the needs of the Armed Forces of Ukraine. M e t h o d s . The main methods of our research are the analysis of literature and technical documents of GNSS observation networks. A systematic review of scientific publications, legislative acts and other documents related to the development of GNSS networks was conducted. R e s u l t s . A significant number of countries have developed their own multifunctional high-precision positioning systems. The creation of the European terrestrial reference system ETRS89, which is available around Europe, became one of the important stages in the development of national networks of reference stations. One of the effective catalysts for the introduction of high-precision positioning systems was the creation of a new structure – the European Positioning System EUPOS. This is a European public initiative aimed at creating a uniform infrastructure in Central and Eastern Europe based on the DGNSS differential method. This technical infrastructure consists of a network of reference GNSS stations and corresponding communication lines. The services of this infrastructure include coordinate support of various accuracy. C o n c l u s i o n s . For further improvement and development of GNSS observation networks, the following aspects should be taken into account: increasing accuracy, ensuring data security, expanding the scope of applications, ensuring reliability and stability of functioning. Regarding the use of GNSS observation networks for defense needs, it is possible to conclude on the expediency of using the services of the Ukrainian permanently operating (permanent) observation network of global navigation satellite systems for geospatial support of troops (forces).